PENGARUH PERCEIVED DESIRABILITY DAN PERCEIVED FEASIBILITY TERHADAP MINAT BERWIRAUSAHA GENERASI Z - Aghivirwiati, Gusti Ayu; Triana Arisanti, Ni Komang; Rindi Antika, Ni Kadek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
The entrepreneurial trend has become a major concern in recent decades, especially because of its role in driving economic growth, creating jobs, and having a positive impact on society and the environment. Entrepreneurial intention research includes theories that focus on predicting entrepreneurial behavior, such as the Theory of Entrepreneurial Events and the Theory of Planned Behavior. For example, perceived desirability and perceived feasibility are factors that influence entrepreneurial intentions. The research was conducted in Petang, Badung Regency. The number of samples used was 210 respondents. The analysis used in the research is SEM PLS. The research results show that Perceived desirability and Perceived feasibility influence Generation Z's entrepreneurial interest in the Petang sub-district in the digital era.